Tax Incentives and Tax Service Quality on UMKM Taxpayer Compliance: In Lamongan Regency - Fikri Nur Rachman; Rita Nataliawati; Rina Sulistyowati (Jurnal Riset Perpajakan: Amnesty, 2022)
This study aims to determine the effect of tax incentives on the quality of taxpayer compliance tax services during the pandemic. The data analysis technique used in this study was multiple regression and the sample was selected using the convenience sampling method so that the researcher chose respondents based on the most easily found or obtained. The data collection method in this study used a questionnaire distributed via a google form link. The number of respondents in this study were 90 respondents who had criteria. The results of this study indicate that tax incentives have no effect on taxpayer compliance while the quality of tax services has an effect on taxpayer compliance